Direct Reprogramming in Bone and Joint Degenerative Diseases: Applications, Obstacles and Directions - Shi, Kesi; Li, Fangcai; Tao, Yiqing; Chen, Qixin (Current Stem Cell Research & Therapy, 2023)
With a booming aging population worldwide, bone and joint degenerative diseases have gradually become a major public health focus, attracting extensive scientific attention. However, the effective treatments of these degenerative diseases have been confined to traditional medications and surgical interventions, which easily lead to the possibility of drug abuse or loss of physiological function to varying degrees. Recently, given that the development of reprogramming has overcome shackles in the field of degenerative diseases, direct reprogramming would provide a new concept to accelerate progress in the therapy of bone and joint degenerative diseases. The process of direct reprogramming would directly induce ordinary somatic cells to the desired targeted cells without passing through pluripotent cell states. In this review, we summarize some direct reprogramming of cells that has been attempted for the repair of common bone and joint degenerative diseases, such as osteoarthritis, osteoporosis-related fracture and intervertebral disc degeneration. However, it is inevitable that some obstacles, such as accurate transcription factors, an appropriate extracellular microenvironment and efficient delivery carriers in vivo, need to be resolved. In addition, developmental and promising directions associated with direct reprogramming have attracted public attention. Investigation of the regulation of the transient genome, metabolic conversion and cellular skeleton would provide superior potential candidates for the revolution of direct reprogramming. The aim of direct reprogramming is to directly provide target cells for cell therapy and even tissue reconstruction in bone and joint degenerative diseases. Moreover, the development of direct reprogramming have potential to achieve repair and even reconstruct in situ, which would be breakthrough effect for the repair of bone and joint degenerative diseases. The advance of direct reprogramming has opened numerous opportunities for new therapeutic strategies in regenerative medicine.
Keywords: Direct reprogramming